Molecular simulation study on effect of mine water hardness on foam stability - Qinggang LU; Kai WANG; Honghu HUANG; Yi LIANG; Jiangshi ZHANG; Yanan WANG; Yulu JIA; Yunfei LIANG (Meitan kexue jishu)
Mine water contains a large amount of hard water ions, and as the main water used in foam dust suppressants, its water hardness is crucial to the dust removal efficiency and economic costs of foam dust suppressants. In order to study the variation law and microscopic mechanism of foam stability influenced by mine water hardness, molecular simulation was employed to investigate the effects of mine waters containing different concentrations of Ca2+, Mg2+, and Na+ on the stability of foam liquid films. Taking a foam system composed of anionic surfactant Sodium Dodecyl Sulfate (MSDS) and nonionic surfactant Alkyl Ethoxylate (AEO-5) in proportional blending as the research object, the variations in surface tension, interface thickness, radial distribution functions, diffusion coefficients, and hydrogen bonds, which are microscopic characterizations, were thoroughly analyzed. The study reveals several findings. Firstly, the interfacial tension of foam systems increases with higher concentrations of Ca2+ and Mg2+, particularly under conditions of high water hardness where foam stability is weakest due to thinner interfaces. Secondly, analysis of radial distribution functions and diffusion coefficients indicates that the oxygen atoms of surfactant head groups are crucial for foam stability, with O1‒3 exhibiting three times greater water adsorption capability compared to O4. In the presence of Ca2+, O1‒3 and O4 exhibit stronger water binding capacities within the foam. Thirdly, different ion types exert varying effects on foam stability. Under conditions of moderate to high water hardness and in the presence of Mg2+, the average hydrogen bond length between O1‒3 and water molecules is shorter than that observed with Ca2+, suggesting stronger hydrogen bonding in Mg2+-containing foams. Conversely, under high water hardness conditions, the average number of hydrogen bonds between O1‒3 and water molecules is fewer and their average bond length greater than in Ca2+-containing foams, indicating enhanced hydrogen bonding strength in Ca2+-based systems at high water hardness. These results deepen our microscopic understanding of how mine water hardness influences foam stability, elucidating microstructural changes and interactions among surfactant molecules and water within foam liquid films.